STUDY OF VOCATIONAL QUALITY ASSURANCE PERFORMANCE IN PREPARATION FOR SCHOOL SELF-EVALUATION IN THE COVID-19 PANDEMIC ERA - Arifin, Zainal; Widodo, Syukri Fathudin Achmad; Wiyono, Giri; Sutikno, Agus; Darmono, Darmono (Department of Mechanical Engineering Education, 2024)
This research is based on the results of initial observations and field observations, such as: (1) the quality of SMK graduates is still low, especially with the current world problem, namely the COVID-19 pandemic. (2) there are still some educational quality standards that need to be improved and even improved their achievements. (3) many vocational high schools have implemented a school quality assurance system, but why is the quality of their graduates still low. The purpose of this study is to determine the assessment of school principals, teachers, school committees, and vocational students to photograph the efforts made by vocational quality assurance, especially in preparing the School Self Evaluation (SSE) as the main capital in the accreditation activities of the school concerned.The research method used is the descriptive quantitative research method. The research population is Vocational High School, while the sample is taking 4 Vocational High Schools that have implemented a Quality Assurance System, especially QMS ISO 9001:2008 or QMS ISO 9001:2015, such as several Vocational High Schools located in the Province of D.I. Yogyakarta and Central Java. Research data were collected based on the results of the distribution of questionnaires (instruments), interviews, observations, documentation studies, and Focus Group Discussions (FGD). The filler of the research instrument is the principals, teachers, school committees, and the concerned vocational students. The research data were analyzed descriptively quantitatively to see how far the level of achievement of the eight National Education Standards (NES) that had been set in the RPS.The results of this study are: (1) schools in implementing a school quality assurance system through their SSE have used four stages, consist of standard-setting, standard fulfillment, continuous evaluation, and quality improvement. (2) schools have taken correct and appropriate steps in achieving their vision and mission based on the formulated SPMI guidelines, (3) schools have implemented eight NESs starting from standards: graduates, content, process, educational assessment, educators and education personnel, educational facilities and infrastructure, education management, and financing standards properly. (4) each vocational high school has the same or different strategies and methods in achieving the school's vision and mission.